The Implementation of Learning Organization to Increasing SME Performance through Innovation - Titiek Ambarwati; Sudarmiyatin Sudarmiyatin; Agus Hermawan (Universitas muhammadiyah malang, 2021)
The resulting performance measures the success of a business. Performance can be said good or not based on several aspects, including conducting continuous learning to improve skills and achieve business goals and innovating to maintain the running business. The objective of this study was to analyze the impact of learning organizations on business performance through innovation as a direct and indirect mediation. This study was conducted in Micro, Small, and Medium Enterprises (MSMEs) in Malang City with a sample of 50 respondents. Data analysis in this study used path analysis with SmartPLS 3.0 software. The results found that the better the implementation of the learning organization, the greater the business performance and innovation. Innovation has a mediating role in the effect of learning organization on performance.